Evidências e ausências da lei N.º 11.645/2008 (história e culturas indígenas) em escolas da rede pública de Ji-Paraná, RO - Silva, Armelinda Borges da (2018)
The work at hand is an integral part of the studies developed within field of the Social Movements, Politics and Popular Education line of research of the Post-Graduation Program in Education (PPGE) of the Federal University of Mato Grosso (UFMT). It proposes to analyze, based on the pedagogical practice of public schools of Ji-Paraná, in Rondônia, how the implementation of law No. 11.645/2008 (history and cultures of the indigenous peoples) happens in a context of coloniality. To accomplish such task, the dissertation is divided in four sections. The first three are anchored in a bibliographic review that discusses the current reality of the region's indigenous peoples and their relationship to school and institutions brought by modern society. The last section is dedicated to the field results obtained with teachers and school students of the public municipal schools of Ji-Paraná. The field data were collected during the months of February to May 2017 using instruments used in a and Participatory Diagnosis (DRP) (WHITESIDE, 1994), such as semi-structured interviews and conversation circles, observation of history curriculum classes and analysis of school documents. The results gathered show an absence of knowledge of the existence of this law and of specific training to act in that field of education. It was also realized that the dissemination and implementation policies still need to be intensified and that there is a need to create new mechanisms to extend the scope of this theme. However, there was a number of identified promising initiatives developed by teachers when working with indigenous history and cultures, such as the invitation for members of a local indigenous community to visit the school and the presentation of videos about the deconstruction of stereotypes and prejudices children can carry on their imaginary. The knowledge of children expressed in drawings emphasize the traditional elements of a "generic Indian" with bow and arrowhead, feathers on head, body paint, thong, bonfire, native hut, etc. Such perception may indicate that, in the local imaginary, only the peoples or individuals who live in the forests can be considered indigenous and not those who live in the social and educational daily life of cities. Regarding textbooks, the use of of small indigenous texts and the mention of several indigenous brazilian peoples appeared to be positive. The contents of the textbooks contribute to the consolidation in the application of the law, but the pedagogical action of teachers needs to be more explicitly in order to relate such content to the local and regional context. In short, the results indicate that the development of this theme in schools can be improved, with a view to implementation and consolidation of law No. 11.645/2008 in the school curriculum.